PENGARUH INTERGOVERNMENTAL REVENUE, KEKAYAAN DAERAH, OPINI AUDIT DAN KEMANDIRIAN KEUANGANTERHADAP PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH - Ulfa Ayu Wulandari (2021)
This study aims to examine the level of mandatory disclosure in regional government financial reports and to examine whether there is a relationship with Intergovernmental Revenue, regional wealth, audit opinion, financial independence. The population in this research was the District/City Government on Nusa Tenggara Island. Sampling was done by census sampling method, amounting to 123 samples, but after the outliers were carried out, there were 117 samples of District/City Government on Nusa Tenggara Island. The test in this study is multiple linear regression using SPSS 25. The test result show that Intergovernmental Revenue, audit opinion, financial independence have no effect on disclosure of financial statement, regional wealth has a negative effect on disclosure of financial statements. Contributions made to local governments is expected to provide benefits in improving the quality of their external communications so as to increase public trust.